Contributos hermenêutico-filosóficos para uma fundamentação ética dos direitos humanos: a epocalidade e o cotidiano sob o pensamento de Heidegger e Gadamer - AROUCK, João Henrique Vasconcelos (Universidade Federal do Pará, 2015)
The present work develops some essential issues of philosophical hermeneutics as a way to fundament human rights in its ethical determination. The discussion is conducted as a hypothesis to face two problems: the representational model of the contemporary scientia juris and its methodologized way of interpretation may not fundament human rights in its proper reason of being. Still, as a consequence, these two problems might be seen as one of the causes to a “rational” but innocuous criticism about human rights as well. Therefore, the philosophical sense of the quotidian – of the “common” – is here discussed as a proper way to analyze the practical routine of law´s everyday interpreters as a pragmatic way to justify the need for human rights in a contemporary law practice. To discuss it, the thematic of intuition is here worked in its existential basis: so, in that way, human rights can be apologized as a substantive part of our intuitions about what is the most fair. Moreover, these fundamental rights can be even thought as a practical way to find out, normatively, the best right – the best law for our epoch. Heidegger leads us to investigate human rights as a necessary event for our time by its ethical significance. In other words: these rights constitute part of the movement of our being-with in its symbolic and suggestive significances. Gadamer help us to interpret that radical philosophical way by hermeneutic terms: to the law reality that idea can be seen as a re-turn to some lost concepts of our humanistic culture. With Gadamer we still can affirm that law is a practical “philosophy” in its most fundamental determinations. Therefore, the Greek disposition for the phronésis is, nowadays, a proper way to see human rights as an ethical manifestation for the best, for the most fundamental goods. Still through the philosophical hermeneutic ideas, we conclude the work with a more specific discussion about the relations between our intuitions, convictions and our pre-conceptual structure which determines the worldness of our concepts into Law´s social practice.